Sunday silence - French, Nicci (William Morrow, an imprint of HarperCollinsPublishers, 2018)
Declared a person of interest when a body is discovered under the floor of her home, London psychologist Frieda Klein realizes that a copycat killer is responsible before she finds herself caught between two obsessive murderers.